The Role of Job Training in Improving Employee Performance - Hidayat, Alhidayatullah; Muh. Abdul Aziz (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
This type of research is descriptive research with a quantitative approach with a questionnaire method. The purpose of this study was to determine the effect of each independent variable, namely training instructors, trainees, training materials, training methods, training objectives and training environment on the work performance of employees. The data analysis technique used is multiple linear regression analysis, based on the partial test of training instructor variables, training materials, training methods, training objectives and training environment there is a positive and significant influence on employee performance while the trainee variable has no significant effect on job performance. employee. Simultaneously (Test F) the training instructor, trainee, training materials, training methods, training objectives and training environment there is a positive and significant influence on employee performance.